Influence of Digital Marketing, Knowledge of Information Technology On the Financial Performance of Small and Medium Enterprises (SMEs) - Sabihaini, Sabihaini; Astuti, Sri; Permana, Rifki Indra; Marita, Marita (RSF Conference Series: Business, Management and Social Sciences, 2021)
The COVID-19 pandemic has lasted almost two years. This has an impact on the sustainability of micro, small and medium enterprises (SMEs). Various efforts have been made to maintain the sustainability of SMEs, one of which is by adopting information technology in their marketing. This study aims to determine the effect of digital marketing, and knowledge of information technology on the financial performance of micro, small and medium enterprises (SMEs) This research is quantitative research. Data was obtained by using a questionnaire. The respondents in this study were SMEs actors in Kapanewon Tempel Sleman Yogyakarta. From the number of SMEs actors who are members of the SMEs Forkom as many as 110 respondents, data is obtained as many as 60 respondents. This study was analyzed using multiple linear regression analysis. Based on the results of data processing, it is known that the use of digital marketing by SMEs actors and SMEs actors’ knowledge of information technology affects financial performance.